Clinical, virologic, and immunologic outcomes in lymphoma survivors and in cancer‐free, HIV‐1–infected patients: A matched cohort study. Issue 15 (26th April 2013) - Spagnuolo, Vincenzo; Travi, Giovanna; Galli, Laura; Cossarini, Francesca; Guffanti, Monica; Gianotti, Nicola; Salpietro, Stefania; Lazzarin, Adriano; Castagna, Antonella
Abstract : BACKGROUND: The objective of this study was to compare immunologic, virologic, and clinical outcomes between living human immunodeficiency virus (HIV)‐infected individuals who had a diagnosis of lymphoma versus outcomes in a control group of cancer‐free, HIV‐infected patients. METHODS: In this matched cohort study, patients in the case group were survivors of incident lymphomas that occurred between 1997 and June 2010. Controls were living, cancer‐free, HIV‐infected patients who were matched to cases at a 4:1 ratio by age, sex, nadir CD4 cell count, and year of HIV diagnosis. The date of lymphoma diagnosis served as the baseline in cases and in the corresponding controls. RESULTS: In total, 62 patients (cases) who had lymphoma (20 with Hodgkin disease [HD] and 42 with non‐Hodgkin lymphoma [NHL]) were compared with 211 controls. The overall median follow‐up was 4.8 years (interquartile range, 2.0‐7.9 years). The CD4 cell count at baseline was 278 cells/mm 3 (interquartile range, 122‐419 cells/mm 3 ) in cases versus 421 cells/mm 3 (interquartile range, 222‐574 cells/mm 3 ) in controls ( P = .003). At the last available visit, the CD4 cell count was 412 cells/mm 3 (range, 269‐694 cells/mm 3 ) in cases versus 518 cells/mm 3 (interquartile range, 350‐661 cells/mm 3 ) in controls ( P = .087). The proportion of patients who achieved virologic success increased from 30% at baseline to 74% at the last available visit in cases ( P = .008) and from 51% to 81% in controls ( P = .0286). Patients with HD reached higher CD4 cell counts at their last visit than patients with NHL (589 cells/mm 3 [range, 400‐841 cells/mm 3 ] vs 332 cells/mm 3 [interquartile range, 220‐530 cells/mm 3 ], respectively; P = .003). Virologic success was similar between patients with HD and patients with NHL at the last visit. Forty cases (65%) and 76 controls (36%) experienced at least 1 clinical event after baseline ( P < .0001); cases were associated with a shorter time to occurrence of the first clinical event compared with controls ( P < .0001). CONCLUSIONS: HIV‐infected lymphoma survivors experienced more clinical events than controls, especially during the first year of follow‐up, but they reached similar long‐term immunologic and virologic outcomes. Cancer 2013 ;119:2710–2719. © 2013 American Cancer Society . Abstract : Human immunodeficiency virus (HIV)‐infected lymphoma survivors reach long‐term immune recovery and virologic suppression similar to what is observed in cancer‐free, HIV‐infected patients. Clinical events are more common among lymphoma survivors, especially during the first year of follow‐up.